PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN TAMU DI HOTEL NIAGARA PARAPAT PROVINSI SUMATERA UTARA - Baetie, Destiana; Yusrizal, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Service quality in a hotel is a very influential on guest satisfaction. The better of the service quality provided the higher the level of guest satisfacation. This study aims to (1) find out how the services at the Niagara hotel parapat (2) to know the satisfaction of guests at the hotel Niagara Parapat (3) to determine the effect of service quality to guest satisfaction at the hotel Niagara Parapat. The sample in this study was 100 people, drawn from the number of guest population at the Niagara hotel by using the accidental sampling technique. Technique of collecting data of this research using questioner. The classical assumption test uses the normality test, multicollinearity test, and heteroscedasticity test. Data analysis technique used in this research is Multiple Linear Regression Analysis. Hypothesis Testing, Multiple Determination Coefficient Analysis (R2). Based on the results of the study known: there is a significant positive effect on the quality of service to the guest papacy at the hotel Niagara Parapat, shown by the results of multiple linear regression analysis Y = 3.341 + 0.306 x1 + 0.012 x2 + 0, 205 x3 + 0.388 x4 + 0.166 x5 + e. F arithmetic (43, 587)> F table (2,311) with significant (0,000) <0.05. The value of coefficient of determination (R2) is 69.9% and 30.1% is separated by other factors not included in this regressi model.Key words: Service Quality, Guest Satisfacation